Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Du syndrome prémenstruel au trouble dysphorique prémenstruel. Une reconfiguration des représentations sur la vulnérabilité des femmes - genrepsy (genrepsy, 2014)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps des femmes; cours; discipline; europe; france; inégalités; justice reproductive; matérialité; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Remettre les pendules à l’heure concernant le Processus de Justice Transformatrice - mysmudge (mysmudge, 2014)
Un article sur la justice transformatrice a été publié il y a quelques jours dans la Presse par Hugo Pilon-Larose avec l’intervention de deux avocat-e-s. Voici une réponse à cet article.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; droits des femmes*; justice réparatrice; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences sexuelles